Preventing relapse to smoking with transcranial magnetic stimulation: Feasibility and potential efficacy. (1st January 2018) - Sheffer, Christine E.; Bickel, Warren K.; Brandon, Thomas H.; Franck, Christopher T.; Deen, Darwin; Panissidi, Luana; Abdali, Syed Amir; Pittman, Jami C.; Lunden, Sara E.; Prashad, Neelam; Malhotra, Ria; Mantovani, Antonio
Highlights: Multiple sessions of 20 Hz rTMS combined with self-help materials is proposed as a treatment for tobacco dependence. The approach is supported by the Competing Neurobehavioral Decisions Systems model. The proposed mechanism of action is increasing activity in the dorsolateral prefrontal cortex. The approach is feasible, well tolerated, and has potential efficacy for cessation. These findings extend the knowledge of treating tobacco addiction with rTMS. Abstract: Many smokers attempt to quit every year, but 90% relapse within 12 months. Converging evidence suggests relapse is associated with insufficient activation of the prefrontal cortex. Delay discounting rate reflects relative activity in brain regions associated with relapse. High-frequency repetitive transcranial magnetic stimulation (rTMS) of the left dorsolateral prefrontal cortex (LDLPFC) increases cortical excitability and reduces delay discounting rates, but little is known about feasibility, tolerability, and potential efficacy for smoking cessation. We hypothesized that 8 sessions of 20 Hz rTMS of the LDLPFC combined with an evidence-based self-help intervention will demonstrate feasibility, tolerability, and potential efficacy in a limited double-blind randomized control trial. Smokers (n = 29), abstinent for 24 h, motivated to quit, and not using cessation medications, were randomized to active 20 Hz rTMS at 110% of Motor Threshold or sham stimulation that replicated the look and sound of active stimulation. Stimulation site was located using the 6 cm rule and neuro-navigation. Multiple clinical, feasibility, tolerability, and efficacy measures were examined. Active rTMS decreased delay discounting of $100 (F (1, 25.3694) = 4.14, p = .05) and $1000 (F (1, 25.169) = 8.42, p < .01), reduced the relative risk of relapse 3-fold (RR 0.29, CI 0.10–0.76, Likelihood ratio χ2 with 1 df = 6.40, p = .01), increased abstinence rates (active 50% vs. sham 15.4%, Χ 2 (df = 1) = 3.80, p = .05), and increased uptake of the self-help intervention. Clinical, feasibility, and tolerability assessments were favorable. Combining 20 Hz rTMS of the LDLPFC with an evidence-based self-help intervention is feasible, well-tolerated, and demonstrates potential efficacy.